Do que você gosta? : epistemologias chiquitanas das comunidades de Nova Fortuna e Seringal, e sua relevância para uma educação intercultural - Paipilla Fernández, Stephany Giovanna (2021)
This academic work is part of the research line Social Movements, Politics, and Popular Education of the Postgraduate Program in Education (PPGE) and the Master's in Education of the Federal University of Mato-Grosso (UFMT) with the support of the Coordination for the Improvement of Higher Education Personnel (CAPES). The focus is on understanding Chiquitan Epistemologies arising from the taste experiences of the Nova Fortuna and Seringal communities, with reference to intercultural education as a right of the indigenous peoples of the municipality of Vila Bela da Santíssima Trindade (MT) and in the Brazil/Bolivia border context. The methodology is grounded in educational research and implements documentary analysis and sensory ethnography as qualitative methods, which is why the author's sensitive experience and her experience as a foreigner were incorporated into the text. It approaches the themes of taste and identity from the dialogue of knowledges to place them outside the colonialism of the biological sciences and social sciences. It positions itself with the indigenous women's movement in Brazil, with anti-colonialism and Chicano studies in understanding the indigenous, border and Vilabelense identity of the Chiquitano People, and with intercultural education as a lens and proposal to reach the reality of the municipal schools “Dom Antonio Rolim de Moura” and “Nova Fortuna”. The text is prepared in Portuguese and Spanish and transversely surveys COVID-19 as a socio-historical event that has affected the feeder educational policies in this context. It contains four chapters: 1) The central lines and weaving for the development of the research; 2) The theoretical axes for thinking about the relationship between taste, identity, and intercultural education in the current context of indigenous peoples in Brazil; 3) The socio-historical dynamics of border identity and socio environmental networks in the taste experiences of the Chiquitano communities of Seringal and Nova Fortuna; and, 4) The hierarchies and inequalities of food education in school meals and school lunch kits implemented in the investigated schools. The results demonstrate that the Chiquitan Epistemologies of the taste experience present a discussion within the social sciences and the health sciences, which remove scientific and universal certainties about identity and taste; we speak of identity and taste processes based on the food culture of the rural Chiquitano border communities, which include sowing cycles, seed conservation, preparation of chicha and patasca linked to women's memories, and consumption rituals linked to families and collective celebrations. The community as a category of affirmation of the Chiquitano People in Vila Bela represents multiple networks and fabrics with quilombolas and migrants from other parts of Brazil who are part of the Agrarian Reform Settlements, and with the farmers and ranchers who have arrived in the place through extractivist and neoliberal policies for the monetization of the Amazon wetlands and the lands in the national border area with Bolivia. The associations and organizations are one of the referents of the networks that are articulated between the Chiquitanos in the city and the communities in the rural space, which are based on the permanence of traditional forms of political organization in tension with the dynamics of power and oppression in these same relations. Finally, food education in rural schools, allowed us to glimpse the complexities of materializing school feeding policies that include the socio-political tensions in the rurality of the municipality, and the possibilities of reinventions in the practices of lunch ladies and teachers for the participation of communities in schools.